Grounds for and order of de novo proceedings in international commercial arbitration - Danilevich, Aliaksandr S. (Journal of the Belarusian State University. International Relations, 2020)
This article considers the procedural issues that arise after the replacement of an arbitrator in an arbitration tribunal. Such replacement raises an issue of the necessity of the case revision by the composition of the tribunal with a new arbitrator. Under the rules of arbitration institutions, this issue has been dealt with in different ways. By means of comparative legal analysis and using the theory of procedural law, the author of the article draws conclusions about the necessity to improve the regulation of this issue in Belarus.
Keywords: arbitration; court; arbitrator; arbitration tribunal; immediacy; rules of procedure; de novo proceedings; commercial